Estrategia lúdicas en el proceso de aprendizaje de matemáticas para los estudiantes de básica superior de la Unidad Educativa El Empalme, Guayas 2021 – 2022. - Palomino Aroca, Marjorie Paola (2022)
The document presents a study on the Playful Strategies in the Mathematics learning process for Higher Basic students of the "El Empalme" Educational Unit, Guayas 2021 - 2022. The research has been developed following a sequential order; starting with the approach of the problem, with the general objective of determining the incidence of the use of playful strategies for learning mathematics in students; For this purpose, the bibliographic search that theoretically supports each of its variables was used. As for the research methodology, this has a non-experimental design, with a sample of 59 students, the types of research used correspond to descriptive, bibliographic and field; For the collection of data, surveys were applied where clear and precise results were obtained from the students who made us know their acceptance towards the inclusion of the ludic within the learning of mathematics; These data served to propose as a proposal a guide of Tics Ludic Strategies with web 2.0 tools for mathematics learning to be applied by upper basic teachers, which will benefit the entire educational community and in particular its students.